Pacing behavior development of youth short-track speed skaters: A longitudinal study - Menting, S. G. P.; Huijgen, B. C.; Konings, M. J.; Hettinga, F. J.; Elferink-Gemser, M. T. (Medicine & Science in Sports & Exercise, 2020)
Purpose This study aimed to analyze the development of pacing behavior of athletes during adolescence using a longitudinal design.